2000
DOI: 10.1074/jbc.m909217199
|View full text |Cite
|
Sign up to set email alerts
|

Therostasin, a Novel Clotting Factor Xa Inhibitor from the Rhynchobdellid Leech, Theromyzon tessulatum

Abstract: Therostasin is a potent naturally occurring tightbinding inhibitor of mammalian Factor Xa (K i , 34 pM), isolated from the rhynchobdellid leech Theromyzon tessulatum. Therostasin is a cysteine-rich protein (8991 Da) consisting of 82 amino acid residues with 16 cysteine residues. Its amino acid sequence has been determined by a combination of techniques, including Edman degradation, enzymatic cleavage, and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) on the native … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 30 publications
0
45
0
2
Order By: Relevance
“…The advantages of such a short peptide are that it would be non-immunogenic and provide higher efficacy in the coagulation cascade. 24) Our results demonstrated that ESP would be an effective, potent FXa inhibitor that might inhibit the bidirectional pathways mediating the coagulation and inflammatory signals. In particular, ESP appeared to directly bind to the active site of FXa, thereby blocking its interaction with substrate.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The advantages of such a short peptide are that it would be non-immunogenic and provide higher efficacy in the coagulation cascade. 24) Our results demonstrated that ESP would be an effective, potent FXa inhibitor that might inhibit the bidirectional pathways mediating the coagulation and inflammatory signals. In particular, ESP appeared to directly bind to the active site of FXa, thereby blocking its interaction with substrate.…”
Section: Discussionmentioning
confidence: 94%
“…All procedures were carried out at room temperature in 96-well microtiter plates following methods described previously, and the concentration for FXa inhibition (5 mg/ml) was also adopted from previously reported studies for antistasin. 20,24) The human enzyme reaction was initiated either by addition of substrate (S-2222, Chromogenix, Milano, Italy) to FXa protein (Novagen, WI, U.S.A.) or to mixtures containing pre-incubated FXa-ASP or -ESP, and the color that developed from the release of p-nitroanilide from the chromogenic substrate molecules was monitored continuously for 5 min at 405 nm on a Spectra Max Plus340 (Molecular Devices, CA, U.S.A.). The progress curves were recorded (% valueϭ[1Ϫ(DOD 405 of each sample/DOD 405 of control)]ϫ100).…”
Section: Synthesis Of Peptidesmentioning
confidence: 99%
“…However, between therostasin and theromin another region is also well conserved; i.e. a consensus sequence has been found in residues 40 - (29) are not conserved in the thrombin inhibitor theromin. Thus, the observed similarities could be the result of an evolutionary divergence from an ancestral gene, arising after gene duplication and able to generate several peptides acting toward specific substrates.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in 1994 the Merck Company deposited foreign patent applications regarding three thrombin inhibitors having masses of 3, 9, and 14 kDa. Interestingly, the N-terminal sequence of the 9-kDa inhibitor, EDDNPGPPRACPGE (47), shows homology with those of theromin (ECENTECPRACPGE), the factor Xa inhibitor therostasin (DCENTECPRACPGE) (29), and the trypsin inhibitor tessulin (MCENTECPRACPGE) (42). This 9-kDa thrombin inhibitor peptide possesses a pI of 4.9, a clotting time in a fibrinogen test of Ͼ600 s/5 l, and a specific activity at the final step of purification of 25 IU for thrombin inhibition and 0.2 IU for factor Xa inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation